Potency of Face Mask-Degrading Bacteria Isolated from Parangtritis Beach, Yogyakarta, Indonesia - Rakhmawati, Anna; Octavia, Bernadetta; Marwati, Siti (Iraqi Journal of Science, 2024)
During the COVID-19 epidemic, improperly discarded face masks turned out to be a severe source of environmental contamination that threatened lives. Bacteria are a crucial degrading agent for face masks. The objective of this study was to isolate and characterize potential face mask-degrading bacteria from discarded face masks at Parangtritis Beach in Yogyakarta, Java, Indonesia. Mineral Salt Media (MSM) containing face mask (black duckbill, blue surgical and white KF94) was used to select bacterial growth ability. The process of face mask degradation was also assisted by scanning electron microscopy (SEM) examination. Eight bacterial strains, designated AP1 through AP8, were obtained using an enrichment screening technique. AP1-AP3, AP4-AP5, and AP6-AP8 were identified phenotypically as Bacillus sp., Pseudomonas sp. and Staphylococcus sp. respectively. Bacillus sp. (AP1) displayed the highest growth (OD600 0.78) on all test conditions among the eight isolates. Moreover, this strain could be grown on MSM-face mask media with a pH range of 5 - 9; temperature 5 – 50°C, and NaCl concentration of 2.5 - 7.5%. The SEM study revealed morphological alterations in the face masks inner, middle and outer layers after interaction with Bacillus sp. This research proved that Bacillus strains could be viable candidates for face mask biodegradation.